Sideband four-mode entanglement in a Four-wave mixing process - Celis, Raul Leonardo Rincon (2022)
We present a detailed characterization of the entanglement in a stimulated Fourwave mixing process. This process is widely studied by the homodyne detection, a technique insensitive to the details of the sideband modes of the involved beams. The emission profile of the FWM process in atomic media shows an imbalance in the amplification of the sidebands, which suggest an asymmetry in the entanglement of the generated states, that can not be observed by the homodyne detection. The stimulated FWM consists on a single frequency pump and a seed beam interacting with the hot rubidium atoms, generating a pair of entangled states, the probe and the conjugated. By the implementation of the resonantor detection, we revealed the hidden entanglement structure of the generated beams. We found that the usual characterization of the state through the homodyne detection is incomplete. On the contrary, the reconstruction of the covariance matrix from the resonant detection allows the full characterization of the quantum correlations and a more complete entanglement structure between the sideband frequency modes. Therefore, with the measurement using resonant detection over a Four-wave mixing process, we can demonstrate the advantage of the detection to reveal entanglement that would be hidden if the usual two-mode description is used.